Riverside Communities: socio-spatial aspects along the Tapajós River - Ravache, Rosana Lia; Godoy, Jeane Aparecida Rombi de; Palmisano, Angelo; Salmoria, Fabiana Zili (Revista Nacional de Gerenciamento de Cidades, 2023)
This essay presents a reflection on the negative consequences that have been affecting riverside communities on the Tapajós River resulting from the transport of commodities on barges. Faced with situations that are as or more harmful to the survival of the riverside population, space was opened to analyze other harmful actions that are substantially affecting the indigenous population, due to the increase in the movement of vessels to meet the demand of agribusiness which, in some way, encourages the criminal transport of wood, resulting from illegal deforestation and contributes to the flow of gold, produced mainly by illegal mining, in addition to the drug trafficking movement, facilitated by streams that disorient control systems and transform the Amazon basin into a transshipment area to give flow to cocaine produced in neighboring countries. The dichotomy that exists today in the context of Amazonian territorial planning justifies the interest in researching how these riverside communities have survived, circumstantially removed from their habitat in socioeconomic conditions that are not favorable to the adaptations imposed by capital. Thus, it is being discussed, objectively, human actions aimed at mitigating the damage that has been caused in the areas covered by Lower Tapajós.